The Place of Theatre Semiotics in Darko Suvin"s Theory for Literary Criticism - Čale Feldman, Lada (Array, 1996)
The article deals with the theoretical heritage and the actual scientific position of a Croatian literary and cultural critic Darko Suvin, emphasising the role of the analysis of theatrical interaction within his critique of a linguistics-inspired approaches to literary phenomena.